The Effect Of Discovery Learning Model Preceded By Making Concept Map Homework On Students’ Learning Competencies At Grade VII In Junior High School 16 Padang - Nofianti Nofianti; Helendra Helendra; Yosi Laila Rahmi Laila Rahmi; Ristiono Ristiono (Universitas Negeri Padang, 2020)
The low level of students’ science learning competencies at grade VII in Junior High School 16 Padang is caused by several factors, one of them is the learning process still used teacher-centered, so the students tend to inactive in the learning process. Therefore, it is necessary to conduct an innovative learning process in order to improve students’ competencies, knowledge, attitudes and skill. One of the method that can be used by the teacher is by implementing the Discovery Learning Model preceded by making concept map homework. Making concept map homework is expected can improve students’ learning activities in science. The aim of this study is to determine the effect of the Discovery Learning model preceded by making concept map homework through students’ learning competencies in science (knowledge, attitudes and skill) at grade VII in Junior High School 16 Padang. Based on the hypothesis, it is known that the knowledge competency tcount > ttable (5,96 > 1,67), the attitude competency tcount > ttable (6,36 > 1,67) and the skill competency tcount > ttable (1,69 > 1,67). The result of the study show that the hypothesis is accepted. Thus it can be concluded that the implementation of the Discovery Learning model preceded by the making concept maps homework can improve students’ science learning competences (knowledge, attitudes and skill) at grade VII in Junior High School 16 Padang.